Dispositional optimism and business recovery during a pandemic. - Mario Amore; Orsola Garofalo; Victor Martin-Sanchez (PLoS ONE)
A large literature at the crossroads of biology and cognitive psychology has shown that individuals hold generally positive expectations about future events. Despite this evidence, to date it remains unclear whether optimism has positive or negative implications for entrepreneurial activities. We examine this question in the context of the Covid-19 pandemic, which provides a unique way to study the role of optimism on the (in)ability of firms to overcome exogenous shocks. Using a large-scale longitudinal survey covering 1,632 UK firms, we find that entrepreneurs who score high on optimism were more likely to innovate and make organizational changes to their firms during the Covid-19 outbreak. Moreover, optimistic entrepreneurs experienced higher revenue growth during the pandemic. Collectively, our study sheds light on one of the psychological factors explaining why some firms can prosper and some others struggle in the wake of an external shock.